Chinese EFL Students' Perceptions of Classroom Justice: The Impact of Teachers' Caring and Immediacy - Yan, Ping (Frontiers in Psychology, 2021)
The correlation between students’ perceptions of three dimensions of classroom justice, teacher immediacy, and teacher caring has been found important since it can provide a learning ambiance for students in which they can enthusiastically learn a new language. To find out this relationship, the present study has strived to probe into the interplay between the aforementioned variables and to see whether teacher caring and teacher immediacy can predict students’ perception of justice. In so doing, the participants of this study were 1178 Chinese EFL students of various ages and education levels. Three instruments were utilized in this study to perceive the students’ perception of classroom justice, teacher immediacy, and teacher caring. To collect the data, these instruments were distributed through an online survey software called Wenjuanxing (Questionnaire Star). Results demonstrated that there was a positive association among these three variables, and utilizing SEM analyses, it was found that both teacher immediacy and teacher caring predict students’ perception of classroom justice that implies teachers who are found to be more caring and give appropriate verbal and non-verbal immediacy where needed, are perceived to change the students’ understanding of the classroom justice to a positive attitude. Finally, the results of this study were discussed regarding previous findings, and accordingly, some implications were put forward in the EFL context.